2009
DOI: 10.1080/08993400903255218
|View full text |Cite
|
Sign up to set email alerts
|

Coping with abstraction in object orientation with a special focus on interface classes

Abstract: One of the subjects that undergraduate students learning Object Oriented (OO) design find hard to apply is the construction of class hierarchies in general, and the use of interface classes in particular. The design process requires decomposition and reconstruction of problems in order to model software classes. The common attributes and behaviors are usually modeled using class inheritance except when the common behaviors do not belong to the same class hierarchy; in such case, an interface class is preferred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
5
7
0
Order By: Relevance
“…The students had difficulties in exhibiting high levels of assimilation concerning a proper design for a hierarchy of exceptions. These results are in line with previous research regarding the object-oriented design capabilities of novice programmers (Lavy et al, 2009;Or-Bach & Lavy, 2004;Sim & Wright, 2001). …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The students had difficulties in exhibiting high levels of assimilation concerning a proper design for a hierarchy of exceptions. These results are in line with previous research regarding the object-oriented design capabilities of novice programmers (Lavy et al, 2009;Or-Bach & Lavy, 2004;Sim & Wright, 2001). …”
Section: Discussionsupporting
confidence: 82%
“…In addition, to be able to construct an adequate class hierarchy, the student must demonstrate a high level of abstraction. Previous research has shown that few students are able to do this (Lavy, Rashkovits, & Kouris, 2009;Or-Bach & Lavy, 2004). …”
Section: Machineoperationexception)mentioning
confidence: 99%
“…The students had difficulty exhibiting high levels of understanding concerning the following: use of multiple exceptions; flow of control in the context of exceptions; handling exceptions further up the calling chain; catching and handling hierarchically related exceptions; and overriding methods that throw exceptions. These results are consistent with previous research regarding the object-oriented design capabilities of novice programmers (Lavy, Rashkovits, & Kouris, 2009;Or-Bach & Lavy, 2004;Sim & Wright, 2001). …”
Section: Discussionsupporting
confidence: 83%
“…For example, Seppa¨la¨, Malmi, and Korhonen (2006) emphasize that data structures and algorithms is challenging to learn for most students and many of them have various types of misconceptions. The reader may find similar statements regarding the complexity and difficulty of domains such as object oriented programming (Lavy, Rashkovits, & Kouris, 2009), debugging (Fitzgerald et al, 2008), and algorithm efficiency and complexity (Gal-Ezer, Tamar Vilner, & Ela Zur, 2004). We believe that instructors should be cautious on the impact that rich learning tasks (here implementing peer reviewing) may have on student learning in such complex domains.…”
Section: Theoretical Backgroundmentioning
confidence: 93%